ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRICE EARNING RATIO (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia 2007-2010) - Nurseto Aji, Meygawan; Rini Demi Pangestuti, Irene (Faculty of Economics and Business Diponegoro University, 2012)
One of theÂ fundamental analysis that usually used by investors and security analize to value the stock price is by price earning ratio(PER) approach. Price earning ratio shows how much investors are willing to pay per rupiah of companies profit. This research have as a purpose to examine influence factors of debt to equity ratio (DER), return on equity (ROE), dividend payout ratio (DPR), price to book value (PBV), current ratio(CR), firm size to price earning ratio(PER) The samples using 26 companies on manufacturing companies sector. Type of data is secondary data from each manufacturing companies listed on the Indonesia Stock Exchange for four years in 2007, 2008 2009, and 2010. The samples are taken by purposive sampling. Data analysis use multiple regression analysis, method which initial by classical test for normality, multicollinearity test, heteroskedastisitas test and autocorrelation test. Hypothesis test is using the F test and t test Results show that variable return on equity (ROE) have negative and significant effect on price earning ratio, price to book value (PBV) and firm size have a positive and significant effect on price earning ratio manufacturing company share. However variable debt to equity ratio (DER), dividend payout ratio (DPR) and current ratio(CR) have no significant effect on price earning ratio manufacturing companies stock.